Up-regulation of miR-20a weakens inflammation and apoptosis in high-glucose-induced renal tubular cell mediating diabetic kidney disease by repressing CXCL8 expression. (2nd November 2022) - Bai, Yang; Li, Hua; Dong, Jie
Abstract: In our study, we determined the pattern of expression and biological roles of microRNA-20a (miR-20a) in diabetic kidney disease (DKD). The difference in the expression of miR-20a and proinflammatory genes (TNF-α, IL-6, and IL-1β) was measured across control, normal glucose (NG), and high glucose (HG) groups. Co-transfection miR-20a mimic and CXCL8 silence was used to assess the miR-20a/CXCL8 axis in the HG-induced HK-2 cell injury involved in DKD. miR-20a in HG group was significantly decreased, and a marked augmentation of inflammatory factor gene expression (TNF-α, IL-6, and IL-1β) in HK-2 cells was induced by HG. miR-20a over-expression enhanced cell proliferation, inhibited cell apoptosis, and suppressed the inflammatory response of HK-2 cells. CXCL8 knockdown strengthened the role of miR-20a. Our findings showed that miR-20a might be a significant regulator of HG-induced renal proximal tubular inflammatory injury mediating diabetic kidney disease through regulation of the expression of CXCL8 and the MEK/ERK pathway.